Inter Vivos Transfers of Ownership in Family Firms - James R. Hines Jr.; Niklas Potrafke; Marina Riem; Christoph Schinke (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper examines the determinants of inter vivos (lifetime) transfers of ownership in German family firms between 2000 and 2013. Survey evidence indicates that owners of larger firms, and firms with strong current business conditions, transfer ownership at higher rates than others. When a firm's self-described business condition improves from “normal” to “good” the likelihood of an inter vivos transfer increases by 46 percent. Inter vivos transfer rates also rose following a 2009 reform that reduced transfer taxes. These patterns suggest that transfer taxes significantly influence rates and timing of in-ter vivos ownership transfers.
Keywords: H24; D31; D22; 330; inter vivos transfers; transfer taxes; family firms